Legitmasi Nasab dan Strategi Dakwah Habib Ba’alwi dalam Perspektif Muhammadiyah - Hasanudin; Setiarso, Gunawan (Masterpiece: Journal of Islamic Studies and Social Sciences, 2025)
Habib is widely known by the Indonesian Muslim community as a descendant of the Prophet Muhammad SAW. The habaib in Indonesia are descendants of Alwi or better known as Bani Alwi or Ba'alwi who migrated to Indonesia with immigrants from Arab Hadramaut Yemen in the 19th-20th centuries AD. The understanding of habib as a descendant of the Prophet Muhammad SAW, makes the Indonesian Muslim community very respectful, and follows what is ordered because they are afraid of curses and not getting the intercession of the Prophet Muhammad SAW in the afterlife. This understanding is gradually being deconstructed with the research of K.H. Imaduddin Utsman Al Bantani "Measuring the validity of the nashab of habib in Indonesia", which states that the nasab of habib in Indonesia is disconnected from the Prophet Muhammad SAW. K.H. Imaduddin Utsman's research from various nasab books, contemporary books, history books and ancient manuscripts does not explain that Ahmad Bin Isa had a son named Ubaidillah. The polemic of the Habib lineage is getting more lively with the genetic research by BRIN researcher Dr. Sugeng Pondang Sugiharto, S.Si, M.Eng, where the DNA (Deoxyrinbonucleic acid) results of the habibs from Hadramaut Yemen showed haplogroup G which is identical to the Jewish nation, not J1 as the descendants of the Prophet Muhammad SAW throughout the world. The polemic about the lineage of the habibs is also increasingly being discussed on social media, with the circulation of digital traces of the lectures of several habibs that are controversial with the pattern and material of the Prophet Muhammad's preaching. The polemic of the lineage of the habibs is also increasingly being discussed, debated and researched by various groups, both religious figures, historians and academics from various disciplines. Here the author wants to try to discuss the legitimacy of the lineage and material of the Ba'alwi habibs from the perspective of Muhammadiyah's understanding. The methods used in this study are library research and media research.   Abstrak Habib dikenal luas oleh masyarakat muslim Indonesia sebagai keturunan Nabi Muhammad SAW. Para habaib yang ada di Indonesia merupakan keturunan Alwi atau lebih dikenal Bani Alwi atau Ba’alwi yang hijrah ke Indonesia bersama pendatang dari Arab Hadramaut Yaman pada abad 19-20 masehi. Pemahaman habib sebagai keturunan Nabi Muhammad SAW, menjadikan masyarakat muslim Indonesia sangat menghormati, dan mengikuti apa yang di perintahkan karena takut kualat dan tidak mendapat syafaat Nabi Muhammad SAW di akhirat kelak. Pemahaman tersebut sedikit demi sedikit mulai terdekonstruksi dengan adanya penelitian K.H. Imaduddin Utsman Al Bantani “Menakar kesahihan nashab habib di Indonesia”, yang menyatakan nasab habib di Indonesia terputus dengan Nabi Muhammad SAW. Penelitian K.H. Imaduddin Utsman dari berbagai kitab nasab, kitab sejaman, kitab sejarah dan manuscript kuno tidak ada yang menerangkan bahwa Ahmad Bin Isa memiliki anak bernama Ubaidillah. Polemik nasab Habib semakin ramai dengan adanya penelitian genetik oleh peneliti BRIN Dr. Sugeng Pondang Sugiharto, S.Si, M.Eng, dimana hasil DNA (Deoxyrinbonucleic acid) para habib dari Hadramaut Yaman menunjukkan haplogroup G yang identik dengan bangsa Yahudi, bukan J1 sebagaimana keturunan Nabi Muhammad SAW di seluruh dunia. Polemik soal nasab habib pun semakin ramai diperbincangkan di media sosial, dengan beredarnya jejak digital ceramah beberapa habib yang kontroversial dengan pola dan materi dakwah Nabi Muhammad SAW. Polemik nasab habaib juga semakin banyak di bahas, di diskusikan dan diteliti oleh berbagai kalangan baik agamawan, sejarawan maupun akademisi dari berbagai disiplin bidang ilmu. Disini penulis ingin mencoba membahas legitimasi nasab dan materi dakwah habib Ba’alwi dari perspektif pemahaman Muhammadiyah. Metode yang digunakan dalam penelitian ini berupa penelitian kepustakaan dan media research